Designing Student Attendance Information Systems Web-Based - Fauziah, Zaleha; Latifah, Haznah; Rahardja, Untung; Lutfiani, Ninda; Mardiansyah, Aditya (Aptisi Transactions On Technopreneurship (ATT), 2021)
Curug SMPN 1 is one of the state senior high schools in Tangerang regency, precisely in Curug district. The teacher absentee system in implementing learning has been running and is considered ineffective because it still has to record in books which are considered inefficient. To facilitate the need for teachers to record reports in books and to make it easier for supervisors, a web-based information system design was created. The method used is a prototype model using the help of an application from Adobe. With the prototype it is expected that the use of the WhatsApp service can be used to provide information to parents. The use of this prototype method is expected to be developed in other schools.